2011
DOI: 10.1080/00220388.2010.527949
|View full text |Cite
|
Sign up to set email alerts
|

Performing Participatory Citizenship – Politics and Power in Kerala'sKudumbashreeProgramme

Abstract: This article examines the operation of Kudumbashree, the Poverty Eradication Mission for the Indian State of Kerala. Kudumbashree operates through female-only Neighbourhood Groups, which aim to contribute to their participants' economic uplift, and to integrate them with the activities and institutions of local governance. As such, Kudumbashree echoes poverty alleviation programmes elsewhere in the Global South designed to link poverty alleviation to 'active citizenship'. This article evaluates the programme, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Furthermore, it is equally important to entail a gendered-perspective for skill development. In fact, there are success stories (such as Kudumbshree, the Kerala State Poverty Eradication Mission) to demonstrate that a gendered-approach towards market oriented and skilled agrarian workers can be an effective approach to enhance the income and nutritional status of households [57,58]. This also implies that the Skill India agenda should focus on mainstreaming agrarian occupations by promoting professional and technical education among those engaged in unskilled and subsistence agriculture and shery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is equally important to entail a gendered-perspective for skill development. In fact, there are success stories (such as Kudumbshree, the Kerala State Poverty Eradication Mission) to demonstrate that a gendered-approach towards market oriented and skilled agrarian workers can be an effective approach to enhance the income and nutritional status of households [57,58]. This also implies that the Skill India agenda should focus on mainstreaming agrarian occupations by promoting professional and technical education among those engaged in unskilled and subsistence agriculture and shery.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, it is consistently reported that social capital and the benefits it generates are undermined by an opportunistic misappropriation of resources (e.g. Nepal: Adhikari and Goldey, ; Indonesia: Silvey and Elmhirst, ; South Africa: Du Toit, ; Malai: Serra, ; Jamaica: Portes and Landolt, ; Malawi and Zambia: Vajja and White, ; Guatemala: Grant, ; Kenya: Grugerty and Kremer, ; India: Williams et al ., ; Jordan: El‐Said and Harrigan, ). The wider social capital literature stresses five elements affecting relationships in developed and developing countries alike: the scope for reciprocal benefit, institutions and the wider social environment, relative resource endowments, interpersonal networks and altruism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also drawn attention to political inteference leading to strained relationships between group members, local bodies and the mission functionaries (John, 2009;Williams et al, 2011).…”
Section: Implementation Of Livelihood Programmes In Indiamentioning
confidence: 99%
“…A major concern especially in earlier programmes has been on the inappropriate programme design leading to faulty selection of beneficiaries, and in many cases the poorest of the poor being left behind (GoK, 2012;Srivastava, 2005;Williams et al, 2011).…”
Section: Implementation Of Livelihood Programmes In Indiamentioning
confidence: 99%